Pragmatic Equivalence of Phatic Utterance in the Indonesian Translation of Pride and Prejudice Novel by Jane Austen - Kasanah, Alimah Nur; Sajarwa, Sajarwa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research explores how phatic utterances, which are important for social interaction in Jane Austen's Pride and Prejudice, are translated into Indonesian. These expressions are challenging to translate because of cultural and language differences, especially when trying to keep their social and emotional meaning. This study identifies types of phatic expressions, looks at the translation methods used in the Mizan Indonesian version, and checks how well the original meaning is kept. It uses a descriptive qualitative approach, comparing dialogues from the English original and the Indonesian translation. The study uses theories on phatic communication (Malinowski, 1923; Jakobson, 1960), translation strategies (Baker, 2018), and pragmatic equivalence (Baker, 1992; Searle, 1969), focusing on what's implied, assumed, and intended. The analysis shows that the translator used several methods. “Cultural substitution" and "paraphrase using a related word” were common for translating greetings, politeness, and small talk. Other methods like "omission" and "loan words" were also used. The study found that the intended purpose of many phatic expressions, like simple greetings and affectionate terms, is usually kept in the translation. The general context of conversations and basic assumptions are also mostly preserved. However, finer details like character-specific implications and the full emotional impact of some original interjections can change or get lost. This often happens when strategies like using more neutral words are chosen.